2020
DOI: 10.1155/2020/6667078
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aromatherapy on Premenstrual Syndrome Symptoms: A Systematic Review and Meta‐Analysis of Randomized Clinical Trials

Abstract: ObjectivesPremenstrual syndrome (PMS) is a common disturbance among women of childbearing age. Aromatherapy is a commonly used form of complementary and alternative medicine (CAM) to treat PMS. The purpose of this study is to quantify and summarize the effects of aromatherapy on premenstrual syndrome symptoms. Methods. PubMed, Scopus, and Cochrane Library databases were searched through relevant search terms until October 2020. The effect sizes were pooled as weighted mean difference (WMD) and 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…According to the evidence, aromatherapy is an effective tool to manage PMS symptoms, in fact, anxiety, depression, and physical symptoms and total score of PMS decrease after odor plants application. 2 This is in accordance with the results expressed in this investigation where all variables showed a decrease after intervention in EG, especially in anxiety which revealed the greatest effect size and percentage of change. Indeed, some studies have found that PMS emotional symptoms decrease after aromatherapy intervention.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the evidence, aromatherapy is an effective tool to manage PMS symptoms, in fact, anxiety, depression, and physical symptoms and total score of PMS decrease after odor plants application. 2 This is in accordance with the results expressed in this investigation where all variables showed a decrease after intervention in EG, especially in anxiety which revealed the greatest effect size and percentage of change. Indeed, some studies have found that PMS emotional symptoms decrease after aromatherapy intervention.…”
Section: Discussionsupporting
confidence: 92%
“…1 This syndrome includes psychological symptoms such as mood swings, anger, irritability, lack of concentration, anxiety, depression, sleep difficulties, between others. 2 Besides, physical symptoms such as headache, fatigue, appetite changes, gastrointestinal symptoms, etc., are present. 3 The intensity of these symptoms may vary between women, affecting their quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many potential therapeutic CAM candidates have been studied in some form, including anise, 97 Echium amoenum, 98 ginger, 99 Melissa officinalis, 100,101 royal jelly, 102 curcumin, 103 Ginkgo biloba, 104 Zataria multiflora, 100,105 Nardostachys jatamansi, 106 Phaleria macrocarpa, 107 oxaloacetate, 108 Neptune Krill Oil, 109 fennel, 110 soy, 111 wheat germ, [100][101][102][103][104][105][106][107][108][109][110][111][112] and lecithin, 113 for the purpose of this review we will cover interventions with the most data available for adult women (Table 3). Similarly, CAM approaches with minimal data available and for which dosing cannot be quantified, specifically aromatherapy, 114 kinesio taping, 115,116 external Qi therapy, 117,118 and Chinese herbal medicine practice 119 are considered outside the scope of this review.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…Research, Society and Development, v. 11, n. 14, e442111436361, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i14.36361 3 Studies report that the inhalation of essential oils is capable of producing changes in physiological parameters [eg. blood pressure, heart rate, muscle tension, pupil dilation, body temperature, blood flow, electrodermal and cerebral activities] (Zhang & Yao, 2019;Es-Haghee et al, 2020;Zhang et al, 2016;Chen et al, 2015). Inhalation and oral administration were two common methods for essential oil manipulation in pre-clinical and clinical trials, while massage was used only in clinical trials with humans and intraperitoneal injection was only used in pre-clinical trials (Zhang N & Yao, 2019).…”
Section: Introductionmentioning
confidence: 99%